Economic policy dilemmas in front of the crisis - Roncaglia, Alessandro (PSL Quarterly Review, 2010)
The article is an introduction to the new issue of the Journal. It provides an overview of the current economic and financial situation and summarises the main topics dealt with by the following articles. Retrenchment of public expenditure is once again being called for by international agencies as well as by leading economists and politicians. The irony of this all is that by rescuing financial institutions the policy authorities, which up to now have totally ignored the problems posed by an excessive increase of private debt, focusing attention on public debt alone, have dealt with a crisis originating in the private debt area by shifting part of its weight to the public sector. This should call for some reconsideration of macroeconomic views. In any case, for any individual country considered in isolation, it is rather difficult to ignore the mainstream recommendations. Countries with already large public deficits and debt risk coming under attack on the side of financial speculation if they ignore the consensus recipes. Financial markets can then foresee a spiral of growing public expenditure for interest payments, growing deficits and growing public debt, further increasing the spread up to the point of collapse. Fiscal retrenchment then takes place, so to say, at gunpoint. There is little choice, thus, for many countries on the sign of their fiscal policies. However, this constraint leaves various options open. JEL Codes: G01, G21, N20